The study of intelligence wireless sensor array to monitor parameter of air - ZHONG Yuan-chang1; TANG Bao-ping2; TAN Chun-lu3; DING Xuan4 (Tongxin xuebao)
A multiple target air parameters monitoring scheme with the help of the wireless intelligence sensor network which is built up with multiple sensors was proposed.The design of the wireless intelligence array sensor was considered,the method to configure the wireless intelligence sensor network was introduced,and the information combination arith-metic of sensor network was provided.Then,a kind of mini-type wireless multiple target air parameters monitoring sys-tem was built up.Experiment result clearly indicates that the system can accomplish the mission of monitoring multiple targets at the same time and the efficiency and reliability,make the air parameter monitoring arrives at a higher level.So the system proposed should be widely used in the domain of air parameter and toxic and harmful gas leakage monitoring.